PEMBENTUKAN KARAKTER DAN KEMAMPUAN BERPIKIR LOGIS SISWA MELALUI PEMBELAJARAN MATEMATIKA BERBASIS SAINTIFIK - I Made Surat (Emasains : Jurnal Edukasi Matematika dan Sains, 2016)
The Formation of Character and Logical Thinking Skills of Students through the learning of Mathematics-based Scientific This article aim to examine the role of mathematics conceptually based scientific in character building and the ability to think logically. Characteristics of mathematics as deductive science and integrated already contain character rules such as; honestly, objectivity, responsibility, thoroughness, perseverance, cooperation, independence and creative. Mathematics as deductive science could use as vehide to train logical thinking, rational, systematic and consistant also obey the principle. Mindset like this is very usefull as a basic of scientific thinking, studying the exact sciences and other social sciences. Through scientific mathematics learning, student’s ability in problem solving and find the patterns also innovate will be trained.